Hochuekkito comprising Atractylodis lanceae rhizoma prevents pulmonary infection of Streptococcus pneumoniae in cyclophosphamide‐treated mice through acceleration of anti‐bacterial protein production. Issue 3 (6th October 2020) - Ideno, Satoshi; Tanaka, Yosuke; Sasou, Kayako; Hosaka, Haruna; Matsui, Hidenori; Maruyama, Hiroko; Tonooka, Miki; Endo, Mari; Nagai, Takayuki; Seki, Hiroyuki; Hanawa, Toshihiko; Ito, Go; et al.
ABSTRACT: Aim: Few pharmacological prophylactics have been developed to prevent lower respiratory tract infection before the onset. Because hochuekkito formula containing Atractylodis lanceae rhizoma (ALR formula) has been shown to enhance the adaptive mucosal immune system of both the upper and lower respiratory tracts, the effect of the formula was investigated on pulmonary infection with Streptococcus pneumoniae and productions of anti‐bacterial proteins as innate protective immunity in lung of immuno‐compromised mice. Methods: Cyclophosphamide (CY)‐treated BALB/c mice were intranasally infected with S. pneumoniae, and effects of hochuekkito formula comprising Hedysari radix and ALR (HR/ALR formula) were evaluated on bacterial counts in lung and lung damage. CY‐treated and untreated mice were stimulated by intranasal inoculation of lipopolysaccharide (LPS), and the effect of administrating HR/ALR‐hochuekkito on the production of anti‐bacterial proteins in the lung was also analyzed. Results: Oral administration of HR/ALR‐hochuekkito (1.5 g/kg) reduced cell counts of S. pneumoniae in bronchoalveolar fluids (BALF) of CY‐treated mice. Bactericidal activity of BALF and mRNA expression of surfactant protein D gene ( Sftpd ) in the lung were significantly increased by HR/ALR‐hochuekkito prior to S. pneumoniae infection. Intestinal manipulation decreased mRNA expression of surfactant protein A gene ( Sftpa1 ) in the lung, and HR/ALR formula improved this impairment. The formula enhanced the production of surfactant protein D and chitinase‐3‐like‐1 in both CY‐treated and untreated mice under LPS stimulation. ALR‐hochuekkito containing Astragali radix (ASR) (ASR/ALR formula) also increased the production of these anti‐bacterial proteins. Conclusion: Prophylactic treatment with ALR‐hochuekkito formula protected immuno‐compromised mice from bacterial pneumonia by enhancing the production of anti‐bacterial proteins such as surfactant protein A/D and chitinase‐3‐like‐1 in the lung.